The Relationship Between Aerobic Endurance and Haemoglobin of Junior High School Football Players 26 Makassar - Mappompo, M. Adam; Arfanda, Poppy Elisano; Aprilo, Ians; Mappanyukki, Andi Atssam; Iskandar, Iskandar (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the relationship between aerobic endurance and haemoglobin levels in soccer players at SMP Negeri 26 Makassar. This research uses quantitative methods with a correlational approach. The research sample consisted of 20 football players who were selected purposively. Aerobic endurance measurements are carried out using appropriate methods, while haemoglobin levels are measured using standard laboratory equipment. Data analysis was carried out using the Pearson correlation test. The results of the study showed that there was a significant relationship between aerobic endurance and haemoglobin levels in football players at SMP Negeri 26 Makassar with a correlation coefficient (R) of 0.308 and a significance value (p) of 0.000 (p < 0.05). There is a positive and significant relationship between aerobic endurance and haemoglobin levels. This shows that the better a player's aerobic endurance, the more optimal the haemoglobin levels in his body, which plays an important role in oxygen-carrying capacity and athletic performance.